Indonesian Teenagers’ Perception of Bengkulu Folklore - Angela, Nofia; Lustyantie, Ninuk; Anwar, Miftahulkhairah (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
The declining interest of young generations in Indonesian folktales has emerged as a concerning cultural issue. This is particularly unfortunate, as folktales represent an intangible cultural heritage embedded with moral values, local wisdom, and cultural identity. This study aims to examine the perceptions of Indonesian adolescents toward Bengkulu folktales, with a particular focus on their understanding of the intrinsic elements that structure the stories, such as characters, setting (place and time), atmosphere, and plot. A descriptive quantitative approach was employed, with data collected through an online questionnaire. Respondents were adolescents aged 11 to 21, selected using convenience and snowball sampling techniques. The findings reveal that adolescents’ comprehension of the intrinsic elements in the folktales Batu Belarik, Batu Dewa, Batu Panco, and Bukit Pabes remains relatively low. The majority of respondents reported lacking an understanding of the key elements in all four folktales. These results indicate that Bengkulu folktales are not widely known among teenagers and have not become part of their daily cultural experience. Based on these findings, more innovative strategies for cultural preservation are needed, such as reimagining folktales in digital and interactive formats, and integrating them into character education curricula. This study is expected to serve as a foundation for designing more effective and relevant cultural preservation programs tailored to younger generations.